Meningkatkan Pemahaman Hubungan Manusia Dengan Lingkungan Atmosfer Dengan Menerapkan Metode Talking Stick Pada Siswa Kelas X di SMA N 1 Tapung - Ermalita, Ermalita (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Thinking how to improve students' understanding of learning about human relationships with the atmospheric environment becomes a challenge in itself to answer it. Various ways and methods of learning have been applied, but the results of the final evaluation semester conducted on the students of grade X SMA N 1 Tapung still not reached KKM which has been determined. The use of talking stick method is expected to increase students' understanding in learning. Using classroom action research on grade X high school students N 1 Tapung and data collected qualitatively and quantitatively it obtained the results of research There is a change in achievement results of student scores that continue above the KKM of 75 with more completeness indicates a fundamental change in student achievement in following the method talking stick on three existing cycle that is from cycle I until cycle III experience of increase. Keywords: Student understanding, talking stick method, human relationship with environment